Application of Micro-Tubing Reeling System to Serial Femtosecond Crystallography - Jihan Kim; Sehan Park; Yunje Cho; Jaehyun Park (Photonics, 2024)
Microcrystal delivery instruments are pivotal to performing serial femtosecond crystallography experiments at the XFEL facilities. We present a novel sample delivery technique based on a micro-tubing reeling system (MRS). Despite the tiny size of the micro-tubing, the MRS device has the advantage of operating without real-time position adjustment of the tube to match with the XFEL pulses. Moreover, the applicable repetition rate is more flexible than the previously reported chip-based one-dimensional fixed target system.